Chronic pain in people living with dementia: challenges to recognising and managing pain, and personalising intervention by phenotype. (9th January 2023) - Collins, Jemima T; Harwood, Rowan H; Cowley, Alison; Di Lorito, Claudio; Ferguson, Eamonn; Minicucci, Marcos F; Howe, Louise; Masud, Tahir; Ogliari, Giulia; O'Brien, Rebecca; Azevedo, Paula S; Walsh, David A; et al.
Abstract: Pain is common in people with dementia, and pain can exacerbate the behavioural and psychological symptoms of dementia. Effective pain management is challenging, not least in people with dementia. Impairments of cognition, communication and abstract thought can make communicating pain unreliable or impossible. It is unclear which biopsychosocial interventions for pain management are effective in people with dementia, and which interventions for behavioural and psychological symptoms of dementia are effective in people with pain. The result is that drugs, physical therapies and psychological therapies might be either underused or overused. People with dementia and pain could be helped by assessment processes that characterise an individual's pain experience and dementia behaviours in a mechanistic manner, phenotyping. Chronic pain management has moved from a 'one size fits all' approach, towards personalised medicine, where interventions recommended for an individual depend upon the key mechanisms underlying their pain, and the relative values they place on benefits and adverse effects. Mechanistic phenotyping through careful personalised evaluation would define the mechanisms driving pain and dementia behaviours in an individual, enabling the formulation of a personalised intervention strategy. Central pain processing mechanisms are particularly likely to be important in people with pain and dementia, and interventions to accommodate and address these may be particularly helpful, not only to relieve pain but also the symptoms of dementia.